Self‐Healing Titanium Dioxide Nanocapsules‐Graphene/Multi‐Branched Polyurethane Hybrid Flexible Film with Multifunctional Properties toward Wearable Electronics. (12th May 2021) - Zhou, Jianlin; Liu, Han; Sun, Yangyi; Wang, Chaoxia; Chen, Kunlin
Abstract: The integration of self‐healing capabilities into flexible electronics arouses extensive attention. The application of self‐healing electronics with multifunctional properties in a variety of exceptional environments has been identified to be significantly challenging and not yet proven to be fully viable thus far. In the present study, the self‐healing octadecane loaded titanium dioxide nanocapsules (OTNs)‐graphene/multi‐branched polyurethane (PU) hybrid flexible multifunctional film is successfully prepared. The prepared film exhibits a novel self‐repair capability that consists of disulfide bonds in the leading chains for efficient self‐healing of PU damage, as well as multiple amino groups in the branches for damage between OTNs‐graphene and PU. Impacted by the constructed self‐healing system and well‐dispersed OTNs‐graphene, the prepared flexible film demonstrates a prominent performance in piezoresistive sensing and a desirable outcome of ultraviolet protection properties, which can effectively prolong its service life, especially when used outdoors. Moreover, the film exhibits thermal insulating properties, capable of offering a suitable route for thermal protection of bio‐integrated wearable electronic devices system. Thus, this self‐healing multifunctional film is promising in wearable electronics, human–machine interaction, artificial intelligence devices, etc. Abstract : A titanium dioxide nanocapsules‐graphene/multi‐branched polyurethane hybrid flexible film intended for wearable sensors is prepared, which is capable of self‐repairing and restoring its piezoresistive sensing property after suffering mechanical damage. The prepared flexible film also has outstanding thermal insulation and UV protection properties due to octadecane loaded titanium dioxide nanocapsules.